QTL Mapping of Heat Tolerance in Cucumber (Cucumis sativus L.) at Adult Stage - Yanyan Liu (Plants, 2021)
Heat stress during cucumber production often leads to sunburn of leaves, growth retardation of stems and roots, fruit malformation, and even plant death, which have a great impact on the fruit quality and yield. However, no studies on the genetic inheritance and quantitative trait locus mapping of heat tolerance in cucumber at the adult stage have been reported yet. In this study, a set of 86 recombinant inbred lines (RILs) derived from “99281” (heat-tolerant) and “931” (heat-sensitive) were used to identify the heat tolerance QTL in summer 2018, 2019, and 2020. Eight-week-old plants were exposed to a natural high temperature environment in the field, and the heat injury index was used to indicate the heat tolerance performance. Genetic analysis showed that the heat tolerance of adult cucumber is quantitatively inherited. One QTL named qHT1.1 on chromosome 1 was identified. It was delimited by Indel 3-3 and Indel 1-15 and explained 59.6%, 58.1%, and 40.1% of the phenotypic variation in 2018, 2019, and 2020, respectively. The efficiency of marker HT-1, which is closely linked to the locus, was tested using 62 cucumber germplasm accessions and was found to have an accuracy of 97.8% in heat sensitive plants. The qHT1.1 was delimited to a 694.5-kb region, containing 98 genes, nine of which may be involved in heat tolerance. Further sequence analysis showed that there are three single-base substitutions within the coding sequences of Csa1G004990. Gene expression analyses suggested that the expression of Csa1G004990 was significantly higher in “99281” than “931” at 14d, 35d, 42d, and 49d after transplanting. This study provides practically useful markers for heat tolerance breeding in cucumber and provides a basis for further identifying heat tolerant genes.